Analisis Pendapatan Petani Tanaman Cabai Di Kecamatan Bengkayang - B01107024, KARTINO EDWARD (Jurnal Pembangunan dan Pemerataan, 2014)
The purpose of the study was to : (1) determine and analyze the income levels of farmers obtained pepper plants in the District Bengkayang, (2) identify and analyze the economic potential created from chili cultivation in the District Bengkayang, (3) determine the constraints as a barrier to cultivation pepper plants in the District Bengkayang. This research was conducted in District Bengkayang for 9 (nine) month in October 2013 - June 2014. Kind of research using survey methods, types and sources of data are primary and secondary. The data analysis technique used is the analysis of net income or profit earned to determine the level of income of farmers and SWOT analysis to determine the potential and the constraints that exist. From the research that has been conducted by the author, it can be concluded that the income level of farmers chili Rp. 483.706.000 with an average Rp. 12.092.650. The main existing economic potential such as soil fertility, the availability of development land chili, chili and marketing potential of the growing need. Major constraints in production are: Availability of fertilizers is still limited, the unavailability of chili processing industry, erratic weather and the price of the game in marketing channels. The role of government intervention in the industrial sector is needed to minimize the weaknesses and threats, as well as the pricing so that the economic imbalance between demand and supply. Strategy development chili in Sub Bengkayang is in quadrant I where support an aggressive strategy that describes the situation very well because there was a power used to achieve profitable opportunities. Â  Keywords: net income, economic potential, farmers' income, weaknesses and threats, development chili of strategy.